ANALYSIS OF TAX PAYMENT COMPLIANCE ON E-COMMERCE TRANSACTION IN SURABAYA - Aloisius Hama (Enrichment : Journal of Management, 2021)
The purpose of this study was to determine the effect of taxpayer awareness, knowledge of tax regulations and tax counseling on e-commerce transaction tax payment compliance.The population in this study are e-commerce actors in the fashion sector who operate on Instagram social media accounts and are domiciled in Surabaya. The analytical model used in this study is Multiple Linear Regression. This analysis model was chosen because this study was designed to examine the effect of the independent variable on the dependent variable. Based on the results of the analyis and discussion, the following conclusions can be drawn: Taxpayer awareness partially has a negative and insignificant effect on compliance with paying taxes by e-commerce actors. Knowledge of tax regulations partially has a significant positive effect on compliance with paying taxes by e-commerce actors. Tax counseling partially has a positive and insignificant effect on compliance with paying taxes for e-commerce actors.